Noncardiac chest pain: The role of costochondritis in differential diagnosis (Research, Society and Development, 2025)
Introduction: Noncardiac chest pain (NCT) is a common complaint in clinical practice, often resulting in emergency consultations. Although the initial investigation aims to exclude cardiac causes, costochondritis represents an important musculoskeletal etiology, often underdiagnosed, whose recognition is essential to avoid unnecessary invasive examinations and provide appropriate treatment. Objective: The present study aims to explore the contribution of costochondritis in the differential diagnosis of NCT, emphasizing its pathophysiology, diagnostic criteria and clinical management. Methodology: An integrative review of the literature was carried out in indexed databases such as PubMed MEDLINE, SCIELO, Ebscohost, Google Scholar and the Virtual Health Library (VHL), using the descriptors "Noncardiac chest pain", "Costochondritis" and "Differential diagnosis". Articles published between 2009 and 2024 were selected, prioritizing clinical studies, systematic reviews, and international guidelines, with critically analyzed data, focusing on clinical presentation, diagnosis, and therapeutic strategies. Results and Discussion: The review demonstrated that costochondritis is responsible for up to 30% of cases of NCDT, with the diagnosis being eminently clinical, based on localized pain on palpation of the sternocostal joints, without systemic inflammatory signs. Treatment includes analgesics, nonsteroidal anti-inflammatory drugs (NSAIDs), and physical measures, with emerging evidence on the use of physiotherapy techniques for symptomatic relief. Conclusion: It is concluded that costochondritis is a relevant cause of NCDT and should be considered in the differential diagnosis, especially after ruling out cardiovascular causes.